Rachel : a sequel to Ellie and Rebecca - Borntrager, Mary Christner, 1921- (Scottdale, Pa. : Herald Press, 1990)
Rachel, youngest child of Mennonite missionaries, visits with Amish grandparents and other relatives.
Young Adult
Keywords: Amish -- United States -- Fiction; Amish -- Fiction; Mennonites -- Fiction; Christian fiction